Gestational exposure to titanium dioxide nanoparticles impairs the placentation through dysregulation of vascularization, proliferation and apoptosis in mice - Zhang L (International Journal of Nanomedicine, 2018)
Lu Zhang,1,* Xingxing Xie,1,* Yigang Zhou,2,* Dainan Yu,1 Yu Deng,1 Jiexiu Ouyang,3 Bei Yang,1 Dan Luo,1 Dalei Zhang,1 Haibin Kuang1,3 1Department of Physiology, Basic Medical College, Nanchang University, Nanchang, 2Department of Color Ultrasonic Room, No 96716 Hospital of PLA, 3Jiangxi Provincial Key Laboratory of Reproductive Physiology and Pathology, Medical Experimental Teaching Center, Nanchang University, Nanchang, Jiangxi, People’s Republic of China *These authors contributed equally to this work Background: Titanium dioxide nanoparticles (TiO2 NPs) have recently found applications in a wide variety of consumer goods. TiO2 NPs exposure significantly increases fetal deformities and mortality. However, the potential toxicity of TiO2 NPs on the growth and development of placenta has been rarely studied during mice pregnancy.Purpose: The objective of this study was to investigate the effects of maternal exposure of TiO2 NPs on the placentation.Methods: Mice were administered TiO2 NPs by gavage at 0, 1 and 10 mg/kg/day from gestational day (GD) 1 to GD 13. Uteri and placentas from these mice were collected and counted the numbers of implanted and resorbed embryo and measured the placental weight on GD 13. Placental morphometry was observed by hematoxylin and eosin staining. The levels of Hand1, Esx1, Eomes, Hand2, Ascl2 and Fra1 mRNA were assessed by qRT-PCR. Uterine NK (uNK) cells were detected by using DBA lectin. Laminin immunohistochemical staining was to identify fetal vessels. Western blotting and transmission electron micrograph (TEM) were used to assess the apoptosis of placenta.Results: No treatment-related difference was observed in the numbers of implanted and resorbed embryos and weight of placenta between the groups. However, 1 mg/kg/day TiO2 NPs treatment significantly reduced the ratio of placenta/body weight on GD 13. The proportion of spongiotrophoblast in the 10 mg/kg/day dose group became higher than that in the control group, yet that of labyrinth was significantly lower in 10 mg/kg/day mice. The expression levels of Hand1, Esx1, Eomes, Hand2, Ascl2 and Fra1 mRNA markedly decreased in TiO2 NP treated placentas. Furthermore, TiO2 NPs treatment impaired the formation of intricate networks of fetal vessels and reduced the number of uNK cells, and inhibited proliferation and induced apoptosis of placenta by nuclear pyknosis, the activation of caspase-3 and upregulation of Bax protein and downregulation of Bcl-2 protein on GD 13.Conclusion: Gestational exposure to TiO2 NPs significantly impairs the growth and development of placenta in mice, with a mechanism that seems to be involved in the dysregulation of vascularization, proliferation and apoptosis. Therefore, our results suggested the need for great caution while handling of the nanomaterials by workers and specially pregnant consumers. Keywords: nanoparticles, titanium dioxide, placenta, proliferation, apoptosis, vascularization